Adjuvant Hormonal Therapy for Low-Grade Endometrial Stromal Sarcoma. (May 2019) - Deshmukh, Uma; Black, Jonathan; Perez-Irizarry, Javier; Passarelli, Rachel; Levy, Karen; Rostkowski, Amanda; Hui, Pei; Rutherford, Thomas J.; Santin, Alessandro D.; Azodi, Masoud; Silasi, Dan-Arin; Ratner, Elena; et al.
Objective: To compare aromatase inhibitors (AIs) with progestins as adjuvant hormonal therapy(AHT) for low-grade endometrial stromal sarcomas (LGESSs). Methods: We reviewed cases with LGESS at our institution from 1984 to 2017. Disease recurrence and recurrence-free survival (RFS) were assessed among patients who received AI, progestins, or no AHT. Results: Among 39 patients with LGESS, 18 received progestins, 13 received AI, and 8 received no AHT. Thirty patients had stage I disease, and 9 had stage II to IV disease. All underwent hysterectomies. Disease recurred in 70% (7/10) of stage I patients who received no AHT, compared to 14.3% (1/7) receiving AI, and 7.7% (1/13) receiving progestins ( P = .003). Among stage I patients taking AI, mean RFS was 153.1 months (95% confidence interval [CI]: 110-195.6) versus 306.2 months (95% CI: 259.7-352.6) for progestin patients and 90.8 months (95% CI: 56.8-124.9) for those who received no AHT. In stage II to IV patients, mean RFS was 148.5 months (95% CI: 148.5-148.5) and 120.8 months (95% CI: 55.8-185.9) for the AI and progestin groups, respectively. All stage II to IV patients received AHT. Among stage I patients, median follow-up time for RFS was 159.1 months for progestin patients, 52.6 months for AI, and 53.1 months for those who received no AHT. Of this, 69% of stage I patients taking progestins reduced/stopped treatment prematurely due to side effects. None of the patients taking AI discontinued treatment early. Conclusion: Aromatase inhibitor is associated with longer RFS in patients with advanced LGESS, is better tolerated than progestins, and can be primary AHT for LGESS.